Historical reconstruction of anthropogenic mercury input from sedimentary records: Yeongsan Estuary, South Korea. (20th December 2015) - Williams, Joshua; Dellapenna, Timothy; Louchouarn, Patrick; Lee, Guan-hong
Abstract: The rapid economic growth of the Republic of Korea (S. Korea) within the last half-century has resulted in a pronounced increase in anthropogenic Hg emission from coal combustion, oil refining, cement production, and waste incineration. The record of increasing atmospheric sources have been investigated with a historical reconstruction of Hg accumulation in 30 sediment cores collected from the Yeongsan Estuary. Within the last several decades, this region has undergone severe anthropogenic alteration, including the construction of an estuarine dam forming the Yeongsan Lake, and installation of numerous seawalls that eliminated vast tidal flats and restricted estuarine circulation. Total mercury concentrations (T-Hg) measured in sediments deposited after 1980 (23.2 ± 9.6 ng g −1 ; n = 273), were significantly higher than those reported for pre-industrial sediments (i.e. background values: 8.6 ± 2.7 ng g −1 ; n = 274). An extensive survey of surface samples show that T-Hg concentrations are highest above the dam, with a gradient to lower values further offshore. The concomitant timing of enrichment of T-Hg within the sedimentary record and increased National emissions in Korea suggests that regional sources dominate the input to the Yeongsan Estuary. This indicates that with sufficient regional historic emission data, T-Hg might be utilized as a geochronologic tool to aid in corroborating traditional radioisotopic methods.